Strengthening Policy Actions and Governance for Nutrition. - Webb, Patrick, 1959-; Pomeroy, Amanda. (Tufts University. Tisch Library., 2017)
Presentation to USAID on stakeholder analysis, and empirical findings from Nepal & Uganda.; Keywords: SPRING, Nutrition Innovation Lab, USAID, Stakeholder Analysis, Nepal results, Uganda resuls Tufts University, SPRING.; NIL Presentations 2013-2015.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy